Balo’s concentric sclerosis – case report - Volpato, Marília Granzotto; Klaus, Daniele Gehlen; Carvalho, Diélly Cunha de; Gomes, Nathalia Tavares; Claudino, Rinaldo (Revista de Medicina, 2007)
Goals: The case described forward search to motivate the medical suspicionin front of a probable diagnose of Balo’s Concentric Sclerosis (BCS) establishing a routine diagnostic. Methods: Case report with cientific review of articles published about the subject. Results: It is really difficult to determine the BCS’s etiology-fisiopathology because of the difuse demyelinating’s areas of the central nervous system (CNS) that are seen in a variety of CNS’s diseases. Magnetic resonance (MR) is very important to the diagnosis of BCS, but the diagnosis’s key is the brain biopsy. The therapy consists of high dose of steroidals being controled by magnetic resonance imaging. Discussion: Once the inflammatory demyelinating nature of the lesion has been established, the difficulty of determination ethiopathology as wide areas of demielynation of the central nervous system can be observed in several neurological diseases. On practice, the BCS’s patients show acute or sub-acute symptoms that suggest expansive brain injury. The disease has an unlikely course, that goes to a quickly evolution in weeks or months without remission until a self-limiting that includes several cognitive symptoms like headaches, aphasia, behavioral disturbance, visual dysfunction and ataxia.